2017
DOI: 10.1097/qai.0000000000001219
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Cash Transfers Improve Retention in PMTCT Services by Mitigating the Negative Effect of Not Having Money to Come to the Clinic

Abstract: Objective To elucidate the mechanisms by which a cash incentive intervention increases retention in prevention of mother-to-child transmission (PMTCT) services. Methods We used data from a randomized controlled trial in Kinshasa, Democratic Republic of Congo. Perceptual factors associated with loss-to-follow-up (LTFU) through six weeks postpartum were first identified. Then, binomial models were used to assess interactions between LTFU and identified factors, and the cash incentive intervention. Results Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…The issue of high loss‐to‐follow‐up immediately after ART initiation has been at the frontline of PMTCT research, since the start of the option B+ era . This would implicate that women who are at the highest risk for non‐adherence tend to drop‐out the soonest.…”
Section: Discussionmentioning
confidence: 99%
“…The issue of high loss‐to‐follow‐up immediately after ART initiation has been at the frontline of PMTCT research, since the start of the option B+ era . This would implicate that women who are at the highest risk for non‐adherence tend to drop‐out the soonest.…”
Section: Discussionmentioning
confidence: 99%
“…One such source of motivation may be the coverage of transport costs upon arrival for routine clinic visits. In a previous study using the same data, Yotebieng et al found evidence suggesting that CCT improves retention by mitigating the cost of clinic attendance [44]. Among women wishing to attend clinic visits as part of routine prenatal or infant care, but who are unable to do so because of travel di culties, CCT could provide enough money to cover the cost of transport.…”
Section: Discussionmentioning
confidence: 99%
“…One such source of motivation may be the coverage of transport costs upon arrival for routine clinic visits. In a previous study using the same data, Yotebieng et al found evidence suggesting that CCT improves retention by mitigating the cost of clinic attendance [22]. Among women wishing to attend clinic visits as part of routine prenatal or infant care, but who are unable to do so because of travel di culties, CCT could provide enough money to cover the cost of transport.…”
Section: Discussionmentioning
confidence: 99%